Prevalence of Loneliness and Its Association With General and Health-Related Measures of Subjective Well-Being in a Longitudinal Bicultural Cohort of Older Adults in Advanced Age Living in New Zealand: LiLACS NZ. (29th June 2022) - Lay-Yee, Roy; Milne, Barry J; Wright-St Clair, Valerie A; Broad, Joanna; Wilkinson, Tim; Connolly, Martin; Teh, Ruth; Hayman, Karen; Muru-Lanning, Marama; Kerse, Ngaire
Abstract: Objectives: There is evidence that loneliness is detrimental to the subjective well-being of older adults. However, little is known on this topic for the cohort of those in advanced age (80 years or older), which today is the fastest-growing age group in the New Zealand population. We examined the relationships between loneliness and selected subjective well-being outcomes over 5 years. Methods: We used a regional, bicultural sample of those in advanced age from 2010 to 2015 (Life and Living in Advanced Age: a Cohort Study in New Zealand). The first wave enrolled 937 people (92% of whom were living in the community): 421 Māori (Indigenous New Zealanders aged 80–90 years) and 516 non-Māori aged 85 years. We applied standard regression techniques to baseline data and mixed-effects models to longitudinal data, while adjusting for sociodemographic factors. Results: For both Māori and non-Māori, strong negative associations between loneliness and subjective well-being were found at baseline. In longitudinal analyses, we found that loneliness was negatively associated with life satisfaction as well as with mental health-related quality of life. Discussion: Our findings of adverse impacts on subjective well-being corroborate other evidence, highlighting loneliness as a prime candidate for intervention—appropriate to cultural context—to improve well-being for adults in advanced age.